From clay to graphene for polymer nanocomposites-a survey - Zaman, Izzuddin; Manshoor, Bukhari; Khalid, Amir; Araby, Sherif (Springer, 2014)
The development of aerospace and automotive in- dustries requests lightweight, high-performance materials, and polymer nanocomposites are ideal candidates in this case, which is shown by the increasingly more publications in this research field over the past two decades. However, the perfor- mance of nanocomposite not only depend on the properties of their individual constituents, but on their morphology and surface characteristics of fillers as well. Selections of nanofillers geometries, e.g. particulate, fibrous or layered have a tremendous influence on the properties of nanocomposites and their processing methods. In this paper, we review the chronological works performed in the field of polymer nano- composites, in particular epoxy nanocomposites reinforced with layered fillers, such as clay and graphene. Surprisingly layered fillers are commercially available and more cost- effective than nanoparticles and carbon nanofibres, and these make them to the most extensively studied fillers that can be geared toward future applications, particularly in large-scale polymer nanocomposite production.